"L'Imago primi saeculi" tra Anversa e Roma - Insolera, Lydia Salviucci (Gregorianum, 2010)
Il contributo ripropone l'atteggiamento culturale, religioso e storico che si intreccia nella storia del famoso libro illustrato, Imago primi saeculi del 1640 ed ha per protagonisti alcuni importanti padri gesuiti tra il Belgio e Roma, come Bollandus. The essay considers the cultural, religious and historical attitudes that are woven together in the narrative of the famous illustrated book, Imago primi saeculi of 1640, and focuses on several important Jesuits from Belgium and Rome, such as Bollandus.